2014
DOI: 10.1016/j.chembiol.2014.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Two-Allergen Model Reveals Complex Relationship between IgE Crosslinking and Degranulation

Abstract: Summary Allergy is an immune response to complex mixtures of multiple allergens yet current models use a single synthetic allergen. Multiple allergens were modeled using two well-defined tetravalent allergens each specific for a distinct IgE thus enabling a systematic approach to evaluate the effect of each allergen and percent of allergen specific IgE on mast cell degranulation. We found the overall degranulation response caused by two allergens is additive for low allergen concentrations or low percent speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Given that patients generate IgE to multiple proteins and multiple epitopes within each protein, the inhibition of responses by only two epitopes highlights that we still know very little about engagement of IgE by complex allergens. In our previous work we demonstrated that low-affinity epitopes can cooperate with high-affinity epitopes in IgE engagement and degranulation responses (32). Moreover, we previously observed that certain peanut epitopes trigger degranulation at significantly lower concentrations of nanoallergens, but when used in combination with an epitope of lower potency, there is a synergistic enhancement of degranulation (12).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Given that patients generate IgE to multiple proteins and multiple epitopes within each protein, the inhibition of responses by only two epitopes highlights that we still know very little about engagement of IgE by complex allergens. In our previous work we demonstrated that low-affinity epitopes can cooperate with high-affinity epitopes in IgE engagement and degranulation responses (32). Moreover, we previously observed that certain peanut epitopes trigger degranulation at significantly lower concentrations of nanoallergens, but when used in combination with an epitope of lower potency, there is a synergistic enhancement of degranulation (12).…”
Section: Discussionmentioning
confidence: 97%
“…Percent degranulation was calculated as previously decribed (32). Briefly, experimental signals were calculated as a percentage between positive control (100%) and negative control (0%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1215 Likewise, in our laboratory, we have demonstrated the importance of weaker affinity epitope during the degranulation response. 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…One well-characterized system is the hapten/Ab pair DNP/anti-DNP IgE. In these systems, small synthetic allergens are often conjugated to a carrier protein, such as BSA (13), a synthetic scaffold (14)(15)(16)(17), or incorporated into liposomes (18). Alternatively, artificial allergens have been generated by grafting IgE epitopes onto a scaffold protein in different numbers and spacings (19).…”
mentioning
confidence: 99%